Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.bpj.2014.11.2369
|View full text |Cite
|
Sign up to set email alerts
|

MmTX1 and MmTX2 from Coral Snake Venom Potently Modulate GABA(A) Receptor Activity

Abstract: electrophysiology in cultured rat striatal neurons and transfected HEK 293 cells. We determined that 79 53% of cultured cells endogenously expressed b3, and 94% of neurons gave tonic-level GABA-evoked currents blocked by phasic concentrations of dopamine (0.1-10 mM). Inhibition was recapitulated in HEK 293 cells transfected with a1b3, a1b3d or a1b2g2 subunits, but we instead observed potentiation in a1b3g2 and a5b3g2. Surprisingly, dopamine (1 mM) evoked rapid currents in a1b2g2, a1b3g2 and a5b3g2 in the absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…CBGA increased the peak currents induced by GABA with a maximum modulation of 271% ( E max 271 ± 40%) and a half maximal effective concentration (EC 50 ) of 910 nM (log EC 50 = −6.09 ± 0.14); however, the modulation was substantially reduced with 30 μM CBGA, so the Hill equation could not be fit when incorporating this high CBGA concentration. Some positive allosteric modulators of GABA A receptors also induce desensitization (Rosso et al, 2015). To determine whether CBGA induced desensitization, we preincubated the receptor with CBGA for 30–180 s before coapplication with GABA (Figure 5e,f).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CBGA increased the peak currents induced by GABA with a maximum modulation of 271% ( E max 271 ± 40%) and a half maximal effective concentration (EC 50 ) of 910 nM (log EC 50 = −6.09 ± 0.14); however, the modulation was substantially reduced with 30 μM CBGA, so the Hill equation could not be fit when incorporating this high CBGA concentration. Some positive allosteric modulators of GABA A receptors also induce desensitization (Rosso et al, 2015). To determine whether CBGA induced desensitization, we preincubated the receptor with CBGA for 30–180 s before coapplication with GABA (Figure 5e,f).…”
Section: Resultsmentioning
confidence: 99%
“…However, similar to the tolerance and GABA A receptor desensitization that is observed with chronic benzodiazepine treatment, prolonged exposure to CBGA resulted in GABA A receptor desensitization, which presents a potential liability with repeated CBGA treatment (Brown et al, 2002; Gallager et al, 1985; Mierlak & Farb, 1988; Nicholson et al, 2018). A previous study has shown that venoms from coral snakes, which are GABA A receptor positive allosteric modulators, also desensitized GABA A receptors in Xenopus oocytes (Rosso et al, 2015). The toxin‐induced desensitization of GABA A receptors correlated with increased neuronal activity and seizures in mice.…”
Section: Discussionmentioning
confidence: 99%
“…We and the authors of Ref. 44 hypothesized that TFTs should bind to GABA A R in a similar manner as ␣-neurotoxins bind to nAChRs. This is supported by their finding that the toxin interaction is decreased upon the H33S mutation in the central loop II of MmTX2 or upon double mutation G228E/Q231K in the receptor loop C. Concerning the binding interface of the toxin, this single mutation agrees with the conclusions we made based on the activity of the chimeric TFT.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although these neurotoxins have no effects in the peripheral nervous system (PNS), even small amounts are highly toxic in the CNS 61 , causing damage in the cerebral cortex, rostrocaudal region of the brain, hemispheric white matter, corpus callosum, fornix, and hippocampus 14 . Similar damage is caused by some three-finger neurotoxins that bind to rat hippocampus-specific muscarinic acetylcholine and A-type γ-aminobutyric acid receptors following jaw paralysis and intense seizures induced by intracerebroventricular injection of venom 61,62 .…”
Section: Biological Activitiesmentioning
confidence: 91%